Superficial Inferior Epigastric Artery: Learning Curve versus Reality. Issue 1 (January 2016) - Sarik, Jonathan R.; Bank, Jonathan; Wu, Liza C.; Serletti, Joseph M.
Abstract : Background: Breast reconstruction with the superficial inferior epigastric artery (SIEA) free flap continues to gain popularity among reconstructive surgeons. The low risk for abdominal wall morbidity must be weighed against the higher concern for thrombotic events. The aim of this study was to review the authors' recent experience with the SIEA flap and investigate whether their previously published incidences of vessel thrombosis and flap loss were related to their own "learning curve" or whether these adverse events are attributable to inherent qualities of the SIEA flap. Methods: The authors performed a retrospective chart review of all patients undergoing SIEA flap surgery between January 1, 2008, and July 1, 2014, at their institution. All included operations were performed by the senior author (J.M.S.). The main outcomes of interest included vessel thrombosis and partial/full flap loss. Results: Forty-seven SIEA flaps were performed on 39 patients. Sixty-four percent ( n = 30) were immediate reconstructions and 79 percent ( n = 37) were bilateral. There were five intraoperative arterial thromboses (10.6 percent) and one intraoperative venous thrombosis (2.1 percent), with eight total thrombotic events (17.0 percent). One total flap loss (2.1 percent) and two partial flap losses (4.3 percent) were experienced. Conclusions: The authors' recent experience with SIEA-based breast reconstruction shows a similar incidence of thrombotic events and flap loss compared with the authors' early experience. These incidences remain greater than what is seen with other abdominally based autologous breast reconstruction techniques and do not appear to be attributable to an operator learning curve. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.